1973
DOI: 10.1113/jphysiol.1973.sp010232
|View full text |Cite
|
Sign up to set email alerts
|

The gustatory sense in foetal sheep during the last third of gestation

Abstract: SUMMARY1. Histological studies revealed that presumptive taste buds are present in the foetal sheep tongue at 50 days. By 100 days the taste buds appear morphologically mature.2. To determine if foetal taste buds are functional, electrophysiological recordings were made of activity in the chorda tympani nerve of sheep foetuses. Single and multi-fibre preparations were studied in foetuses aged 100 days to term.3. Responses were recorded to lingual stimulation with salts, acids, glycerol, glycine, sodium sacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

1977
1977
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…Fetuses were delivered onto a water-circulating heating pad on a table next to the ewe and were covered with cotton pads. Umbilical and placental circulation remained intact, so the fetus was anesthetized through and maintained by the ewe (Bradley and Mistretta, 1973). Ewe and fetus, or postnatal lambs, were deeply anesthetized throughout experiments and received a lethal overdose of anesthetic at the end of experiments .…”
Section: Materials and Methods Animals And Surgical Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetuses were delivered onto a water-circulating heating pad on a table next to the ewe and were covered with cotton pads. Umbilical and placental circulation remained intact, so the fetus was anesthetized through and maintained by the ewe (Bradley and Mistretta, 1973). Ewe and fetus, or postnatal lambs, were deeply anesthetized throughout experiments and received a lethal overdose of anesthetic at the end of experiments .…”
Section: Materials and Methods Animals And Surgical Preparationmentioning
confidence: 99%
“…During the earlier period of accelerated growth of secondorder soma and dendrites, only low-frequency neural impulses are transmitted centrally through peripheral taste afferents (Bradley and Mistretta, 1973;Mistretta and Bradley, 1983). It is very difficult to record successfully from taste afferents younger than 100 days of gestation, and even at 110 days the magnitude of neural responses is small.…”
Section: Development Of Nst Neuron Geometry and Neurophysiological Tamentioning
confidence: 99%
“…An electrophysiological study on the postnatal development of the gustatory system has also been thought necessary for full understanding of the ontogeny of gustatory function.However,neurophysiological studies on the development of taste receptors have been undertaken only by BRADLEY and MISTRETTA(1973),who found that the chorda tympani nerve responses to lingual stimulation by various taste substances in sheep fetuses aged 96 to 137 days are similar to those in lambs and adult sheep.…”
mentioning
confidence: 99%
“…An electrophysiological study on the postnatal development of the gustatory system has also been thought necessary for full understanding of the ontogeny of gustatory function.However,neurophysiological studies on the development of taste receptors have been undertaken only by BRADLEY and MISTRETTA(1973),who…”
mentioning
confidence: 99%
“…A significant incre ase of the ingestion occurs when saccharin is injected in the amnion, and the opposite is detected on iodized oil, a bitter flavor. There f o re, the fetus has pre fe rence for sweet flavor and displeasure with the bitter flavor 10,11 .…”
Section: Discussionmentioning
confidence: 99%